Clinical, Endocrine and Imaging Characteristics of Patients with Primary Hypophysitis - Angelousi, Anna; Cohen, Carolina; Sosa, Soledad; Danilowicz, Karina; Papanastasiou, Lina; Tsoli, Marina; Pal, Aparna; Piaditis, Georgios; Grossman, Ashley; Kaltsas, Gregory (Hormone and Metabolic Research, 2018)
Primary hypophysitis (PH) is a rare disease with a poorly-defined natural history. Our aim was to characterise patients with PH at presentation and during prolonged follow-up. Observational retrospective study of 22 patients was conducted from 3 centres. In 14 patients, PH was confirmed histologically and in the remaining 8 clinically, after excluding secondary causes of hypophysitis. All patients had hormonal and imaging investigations before any treatment. Median follow up was 48 months (25–75%: 3–60). There was a female predominance with a female/male ratio: 3.4:1. Eight out of 22 patients had another autoimmune disease. Headaches and gonadal dysfunction were the most common symptoms. Five patients presented with panhypopituitarism; 17 patients had anterior pituitary deficiency, and 7 had diabetes insipidus. At presentation, 9 patients were treated surgically, 5 received replacement hormonal treatment, and 8 high-dose glucocorticoids from whom 5 in association with other immunosuppressive agents. Six patients showed complete recovery of pituitary hormonal deficiencies while 6 showed a partial recovery during a 5-year follow-up period. No difference was found between patients treated with surgery and those treated medically. The overall relapse rate was 18%. PH can be manifested with a broad spectrum of clinical and hormonal disturbances. Long-term follow-up is required to define the natural history of the disease and response to treatment, since pituitary hormonal recovery or relapse may appear many years after initial diagnosis. We suggest that surgery and immunosuppressive therapy be reserved for exceptional cases.
Keywords: pituitary; hypophysitis; autoimmunity; glucocorticoids